Comparison of percutaneous and cutdown access-related minor complications after endovascular aortic repair - Gomes dos Santos Ferreira Rebelo, Artur Luis; Voss, Patrick; Ronellenfitsch, Ulrich; Sekulla, Carsten; Ukkat, Jörg (Experimental and Therapeutic Medicine, 2022)
groin access, thoracic/endovascular aortic repair, complications, percutaneous, cutdown, life quality